Prevalence and risk factors of hepatitis B virus infection among medical laboratory science students in a Ghanaian tertiary institution - Philip Apraku Tawiah; Albert Abaka-Yawson; Emmanuel Sintim Effah; Kingsley Arhin-Wiredu; Kwabena Oppong (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - This study aimed to determine the prevalence and risk factors of hepatitis B virus (HBV) infection among medical laboratory science students (MLSSs) in the University of Health and Allied Sciences (UHAS), Ghana. Design/methodology/approach - A cross-sectional study design was employed to recruit a total of 178 students into the study. A self-administered questionnaire was used to gather relevant information on risk factors, and a hepatitis B diagnostic test kit was used to test for HBV infection. Descriptive, chi-square test, bivariate and multiple logistic regression statistical analysis were computed. Significance was observed at p < 0.05. Findings - The prevalence of HBV infection among MLSSs was 6.7%. Torn gloves and splash of blood and body fluids contributed to 43.0% and 28.0% of all the risk factors of HBV infection, respectively. Also, 43.3% of students had received at least one dose of the hepatitis B vaccination. Sharp object-related injury and torn gloves increased the odds of HBV infection, while vaccination decreased the odds of HBV infection. Originality/value - This study reveals the prevalence of HBV among MLSSs, who are recognized as being among the high-risk student populations aside from student nurses.